Seeds technologies: performance of sodium alginate and calcium chloride as seed coating - Felipe Bueno Dutra; Justo Dona, Danieli Bianca; Ponce Shiguehara, Ana Paula; Inocente, Mariane Cristina; Terciotti de Oliveira, Andreliza Roberta; Santana da Silva, José Mauro; Conceição Márquez Piña-Rodrigues, Fatima (Acta Biológica Catarinense, 2024)
Direct seeding is a restoration method that can benefit from the use of seed coating techniques to increase efficiency in the field. This study aimed to evaluate the effectiveness of sodium alginate as a seed-encapsulating agent and calcium chloride as a crosslinking agent for a model species. Three concentrations of alginate (1.5%, 2%, and 3%) and two concentrations of calcium chloride (5% and 10%) were used. Encapsulation occurred through a drip process. The treatments consisted of ten replications of ten Solanum lycopersicum L. (Solanaceae) seeds, totaling 600 seeds. We counted the number of seeds emitting radicle (SER), the mean germination time (MTG), the germination speed index (GSI), and the synchronization index (Z). Encapsulation using an alginate concentration of 2% and the lowest concentration of calcium chloride (5%) showed the best results for SER (66±18.5), MGT (10.5), GSI (0.63), and Z (-0.3562). The combination of a 2% alginate concentration with the lowest concentration of calcium chloride (5%) shows potential for applications in seed encapsulation.